Sub-optimum MLSE receiver structures for band-limited nonlinear satellite communications system - Wong, Ee Sing. (2009)
Satellite communications channel suffer from both power and bandwidth limitations. The power limitation necessitates the operation of the satellite transponder TWTA and maybe even the earth station HPA in the non-linear region for maximum power transfer. The non linear amplifications cause non-linear input amplitude to output amplitude conversion characteristic as well as non linear input amplitude to output phase conversion characteristic. Together with the bandlimiting filters, they introduce a complex form of intersymbol interference which is unremovable by linear receiver concepts.